STUDENTS’ PERSPECTIVE TOWARD THE USE OF DIGITAL COMIC IN LEARNING WRITING SKILL - Fernando Fernando; Dyah Aminatun (fsip.teknokrat.ac.id, 2021)
Many instructors and students have used digital comic to enhance their English skills. This research aims to analyze students' perspectives on using digital comic in learning writing skill at the senior high school level. This research employed a qualitative design to gain the data through a questionnaire instrument. The sample of this research was the eleventh-grade students of SMAN 1 Padang Cermin, and 20 students participated in this research. Based on the data result of this study, students had positive feedback toward the use of digital comic to help them develop their multiple English skills and help the students enjoy and increase their interest, especially in learning writing skill of the English language through creating a short English story. As conclusion, the result proved that the use of digital comic could give positive effects on students’ writing skill in eleventh grade. It is also suggested that teachers can apply this learning medium to help them teach writing skill for their students at school.